Two new species and a new record of Omaliini McLeay, 1825 (Coleoptera: Staphylinidae: Omaliinae) from Indonesia - Shavrin, Alexey V. (Zootaxa, 2023)
Two new species of Omaliini McLeay, 1825 from Indonesia are described and illustrated: Nipponophloeostiba explanata sp. n. from Bali and Phloeostiba mamasa sp. n. from Sulawesi. Nipponophloeostiba longilobata Shavrin, 2020 and the genus Phloeostiba Thomson, 1858 are recorded from Indonesia for the first time.